Enhanced biocompatibility and osteogenic ability on amino-modified polyetheretherketone. (1st January 2023) - Qiu, Peng; Dai, Tao; Feng, Le; Liu, Min
Abstract: Polyetheretherketone (PEEK) is a potential implant material for dental application due to its excellent mechanical properties and low elasticity modulus. However, its biological inertia results in weak osseointegration between implants and bone tissue, which limited its clinical application. In this study, amino groups were covalently grafted on the PEEK surface using a simple facile self-assembly method to address its poor osteogenic ability. The surface characterization, cell adhesion, proliferation and osteogenic differentiation of MC3T3-E1 cells on bare PEEK and amino-modified PEEK (PEEK-APTES) were studied. After grafting amino groups onto the PEEK, the surface morphology changed, the contact angle decreased significantly. The PEEK-APTES showed boosted cell adhesion, proliferation, alkaline phosphate (ALP) activity, extracellular matrix (ECM) mineralization, and expression of osteogenic genes in MC3T3-E1 cells. These findings suggested that amino modification significantly improved the biocompatibility and osteogenic ability of PEEK in vitro .